The Role Of The National Universities Commission (Nuc) In The Development Of University Education In Nigeria: Reflections And Projections - ADEOTI, Ezekiel Oladele (Advances in Social Sciences Research Journal, 2015)
Just about two years after Nigeria’s independence, the National University Commission (NUC) was established as an advisory agency on higher education in the cabinet office of the First Republic of Nigeria. The NUC was charged with the responsibility of advising government on financial needs of the universities and to handle the planning of a balanced and coordinated development of university education in Nigeria. These functions were further expanded with the enactment of Decree No. 1 of 1974 that transformed NUC from advisory capacity to a statutory body. This was an outcome of the centralization of university education in the country, during which the Federal Government took over all the then existing regional universities in the country. The expansion of university education in Nigeria reached its nadir in recent time with the efforts by governments, the private sector and faith based organizations establishing new universities and expanding the existing ones. This development brought with it enormous responsibilities and challenges. How the NUC has been able to cope with its new status and its responsibilities is the prime focus of this paper. The paper examines the Nigerian University system before the formation of NUC. It discusses the establishment and role of NUC and evaluates its impact on university education in the country. The paper highlights the challenges that have constrained the operations of the Commission. It concludes by suggesting recommendations that might be of help to overcome the identified challenges and further enhance the development of university education in Nigeria.